Synthesis and characterization of novel copper(II)-sunitinib complex: Molecular docking, DFT studies, Hirshfeld analysis and cytotoxicity studies - Tarasi, Facundo (2021)
The main goal of this work was to report the synthesis, characterization, and cytotoxicity study of a novel copper(II)-sunitinib complex, CuSun. It has been synthesized and characterized in solid state and in solution by different methods (such as DFT, FTIR, Raman, UV-vis, EPR, NMR, etc.). The solid-state molecular structure of trichlorosunitinibcopper(II), where sunitinib: N-[2-(diethylamino)ethyl]-5-[(Z)-(5-fluoro-2-oxo-1H-indol-3-ylidene)methyl]-2,4-dimethyl-1Hpyrrole-3-carboxamide, for short Cu(Sun)Cl3, was determined by X-ray diffraction. It crystallizes in the triclinic space group P-1 with a = 7.9061(5) Å, b = 12.412(1) Å, c = 13.7005(8) Å, α = 105.021(6)◦, β = 106.744(5)◦, γ = 91.749(5)◦, and Z = 2 molecules per unit cell. Also, we have found π-π interactions and classic and non-classic H-bonds in the crystal structure by using Hirshfeld surface analysis. In the speciation studies, the complex has dissociated in protonated sunitinib and chlorocomplex of copper(II), according to1HNMR, EPR, UV-vis and conductimetric analysis. Molecular docking of the complex in both, ATP binding site and allosteric site of VEGFR2 have shown no improvement in comparison to the free ligand. Besides, cytotoxicity assay on HepG2 cell line shows similar activity for complex and ligand in the range between 1–25 µM supporting the data obtained from studies in solution.